Liquid Horizons: Public Art and Cultural Transformation on the Margins - Zimermann, Giovana Aparecida Zimermann (Farol, 2025)
This article proposes a reflection on contemporary public art in river and coastal territories, based on three axes: sensitive cartographies of the margins; underwater installations and relational art; and the monument as a symbolic gesture in the face of climate change. Emblematic works are analyzed, such as Roberto Burle Marx's Copacabana Sidewalk; Mark Manders's Fragment of a Living Room Reduced to 88% (2001); Christo and Jeanne-Claude's floating walkways; and Jason deCaires Taylor's underwater museums. These experiences are complemented by the installation COP 30: The Future in Suspension, by the researcher, conceived as situated public art sensitive to environmental urgency. In all these works, art emerges as an aesthetic-political device that reinscribes meanings in the territories of the margins—marine or river—activating memories, affections, and possibilities for re-enchanting the world. By engaging the body and the collective, these artistic practices expand the symbolic field of public space and contribute to imagining new pacts between society and nature.
Keywords: public art; artistic installation; relational art; ecology and aesthetics; coastal territories